The Influence of Celebrity Endorsers and Product Quality on Repurchase Intention of Timephoria Cosmetics in Mataram City Moderated by Consumer Satisfaction - Elvarah Sandova; Lalu Adi Permadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The halal cosmetics industry in Indonesia is growing rapidly with a market value of USD 7.8 billion in 2022, but Timephoria customer retention in Mataram City is still below national standards, creating a research gap regarding the influence of celebrity endorsers and product quality on repurchase intentions moderated by consumer satisfaction. This study aims to examine this relationship to provide marketing strategy recommendations. Using a quantitative explanatory approach with a causal survey method and SEM-PLS, the population included Timephoria consumers in Mataram aged ≥17 years, with a sample of 250 respondents via purposive sampling through Google Forms on social media. The 5-point Likert scale questionnaire instrument was tested for validity (outer loading >0.7, AVE >0.5) and reliability (CR >0.7, Cronbach's α >0.7) using SmartPLS 4.0, analyzed through outer/inner models, R-square, and bootstrapping. The results show that product quality (β=0.369, t=4.283, p<0.001) and consumer satisfaction (β=0.489, t=6.131, p<0.001) have a significant effect on repurchase intention (R²=0.787), while celebrity endorser (t=1.178, p=0.239) and moderation are not significant. The conclusion recommends prioritizing halal product innovation and customer service for optimal retention.